A qualitative study: the perception on anti-smoking campaign among smokers in Kuantan - Md Isa, Muhammad Lokman; Alias, Normalina; Mat Yusof, Afzan; Jaafar, Mohamad Helmy (Penerbit Universiti Kebangsaan Malaysia, 2020)
Smoking is an inevitably unhealthy habit among Malaysian that could harm not only the smokers but also the community. Even though there are a lot of anti-smoking campaign had been introduced by the government but the effectiveness is still marginal. Thus, the objectives of this study were to explore the main factor related to the failure of anti-smoking campaign in Malaysia, to explore the effectiveness of “Smoking Cessation Clinic” and to discover the best solution to ensure the campaign is effective in the future. This is a qualitative cross-sectional study. Interviews were conducted among five voluntary respondents which were smokers and ex-smoker at Public area and selected smoking cessation clinics in Kuantan. This study used thematic analysis to analyse the data. This study found that few contributing factors from the perspective of smokers need to be prioritised by higher authority for improvements. Those contribution factors are minimal creativity on managing anti-smoking promotion, low self-awareness about health, demand on energizer at workplace and poor stress management. Findings recommend that the campaign shall start from primary and secondary school, improvise warning sign of disease, widening the promotion area, provides reward during campaign and smokers to take initiative to involve in the program. Furthermore, the government also needs to focus on the prevention of start smoking rather than the intervention to quit smoking that may cost lots of financial demand. ********************************************************************************* Tabiat merokok adalah perilaku yang tidak sihat malah membahayakan bukan sahaja diri sendiri malahan masyarakat sekeliling. Walaupun terdapat banyak kempen anti-merokok telah diperkenalkan oleh kerajaan, namun keberkesanannya masih di tahap rendah. Oleh itu objektif kajian ini adalah untuk meneroka faktor utama kegagalan kempen anti-merokok di Malaysia, meneroka keberkesanan “Klinik Berhenti Merokok” dan menemui penyelesaian terbaik untuk memastikan kempen yang dijalankan berkesan pada masa akan datang. Ini adalah kajian rentas kualitatif di mana temuduga dijalankan di kalangan lima sukarela responden yang terdiri dari perokok dan bekas perokok di kawasan awam dan tiga klinik berhenti merokok yang terpilih. Data dianalisis dengan menggunakan analisis bertema. Kajian ini mendapati beberapa faktor penyumbang dari perspektif perokok dan pihak berkuasa perlu diberi keutamaan untuk penambahbaikan iaitu kurang kreativiti yang minimum dalam menguruskan promosi anti-merokok, kurang kreatitivi dah terhadap kesihatan, permintaan bahan pencetus semangat di tempat kerja, dan dalam pengurusan tekanan yang lemah. Hasil kajian mengesyorkan bahawa kempen bermula di sekolah rendah dan menengah, improvisasi tanda amaran penyakit, meluaskan kawasan promosi, memberi ganjaran semasa kempen dan perokok perlu mengambil inisiatif melibatkan diri dalam program ini. Kerajaan perlu menumpukan perhatian kepada program pencegahan merokok terlebih dahulu, daripada program intervensi berhenti merokok yang mungkin melibatkan kos kewangan yang tinggi.